2000
DOI: 10.21236/ada382164
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Utah and DoDPI Scoring Accuracy: Equating Veracity Decision Rule, Chart Rule, and Number of Data Channels Used

Abstract: The public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collectior of information, including suggestions for reducing the burden, to Department of Defense, Washington Headquarters Services, Directorate for I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Rules for numerical scoring developed independently at the University of Utah further reduced the number of criteria to 10 (Bell et al, 1999). Consistent with the idea that fewer is better, Senter, Dollins, and Krapohl (1999) found that evaluations based on Utah criteria were more reliable and more valid than those based on DoDPI criteria.…”
Section: Introductionsupporting
confidence: 52%
See 3 more Smart Citations
“…Rules for numerical scoring developed independently at the University of Utah further reduced the number of criteria to 10 (Bell et al, 1999). Consistent with the idea that fewer is better, Senter, Dollins, and Krapohl (1999) found that evaluations based on Utah criteria were more reliable and more valid than those based on DoDPI criteria.…”
Section: Introductionsupporting
confidence: 52%
“…Truthful suspects' veracity had been established by the subsequent confession of another individual that cleared the suspect of any wrongdoing. Deceptive suspects' veracity had been established by their own admission that they had lied to the relevant questions sometime after they had taken the polygraph test or by irrefutable physical evidence (Dollins et al, 1999).…”
Section: Polygraph Casesmentioning
confidence: 99%
See 2 more Smart Citations